New-generation platinum agents for solid tumors. (February 2009) - Shah, Neel; Dizon, Don S
Cisplatin was one of the first chemotherapeutic agents to exhibit broad efficacy in solid tumors and it remains among the most widely used agents in the treatment of cancer. Its introduction inspired great efforts to design similarly effective platinum agents that overcome the three main limitations of cisplatin: toxicity, tumor resistance and poor oral bioavailability. However, 40 years after the initial discovery of cisplatin, only two platinum agents have garnered US FDA approval: carboplatin and oxaliplatin. Although hundreds of promising agents were tested in clinical trials during the 1990s, only oxaliplatin made it past clinical development. For a brief period, the economic cost of these unsuccessful efforts retarded further efforts to develop new agents. However, two exciting platinum agents have been brought to Phase III trials: satraplatin in hormone-refractory prostate cancer and picoplatin in small-cell lung cancer. If successful, they may inspire a new effort to bring better-designed platinum agents to market. This article reviews the clinical development of platinum agents to date and speculates on the role of platinum agents in the near future.